2021
DOI: 10.1111/mec.16300
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in high temperature‐regulated gene expression predicts evolution of plasticity with climate change in the scarlet monkeyflower

Abstract: A major way that organisms can adapt to changing environmental conditions is by evolving increased or decreased phenotypic plasticity. In the face of current global warming, more attention is being paid to the role of plasticity in maintaining fitness as abiotic conditions change over time. However, given that temporal data can be challenging to acquire, a major question is whether evolution in plasticity across space can predict adaptive plasticity across time. In growth chambers simulating two thermal regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 104 publications
(137 reference statements)
0
6
0
Order By: Relevance
“…Motivated by current debate surrounding the Trade-off Hypothesis and increasing interest in the evolution of phenotypic plasticity and genetic assimilation under global change (Gunderson and Stillman 2015;Kelly 2019;Sasaki and Dam 2019;van Heerwaarden and Kellermann 2020;Barley et al 2021;Sasaki and Dam 2021;Preston et al 2022), we used simulations to explore the more general consequences of regression to the mean for tests of genetic assimilation at the macroevolutionary level. We conducted simulations that assumed mechanistically different models for plasticity evolution, as well as different experimental sampling designs for measuring species phenotypic traits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by current debate surrounding the Trade-off Hypothesis and increasing interest in the evolution of phenotypic plasticity and genetic assimilation under global change (Gunderson and Stillman 2015;Kelly 2019;Sasaki and Dam 2019;van Heerwaarden and Kellermann 2020;Barley et al 2021;Sasaki and Dam 2021;Preston et al 2022), we used simulations to explore the more general consequences of regression to the mean for tests of genetic assimilation at the macroevolutionary level. We conducted simulations that assumed mechanistically different models for plasticity evolution, as well as different experimental sampling designs for measuring species phenotypic traits.…”
mentioning
confidence: 99%
“…2021; Sasaki and Dam 2021; Preston et al. 2022), we used simulations to explore the more general consequences of regression to the mean for tests of genetic assimilation at the macroevolutionary level. We conducted simulations that assumed mechanistically different models for plasticity evolution, as well as different experimental sampling designs for measuring species phenotypic traits.…”
mentioning
confidence: 99%
“…Our results underscore that the evolution of phenotypic plasticity can be an important, though somewhat underexplored empirically, driver of trait change on decadal to centennial timescales. Appreciation for its potential importance has likely been limited in part because the evolution of plasticity can be challenging to assess, which can be overcome by leveraging ‘resurrection ecology’ approaches (Preston et al ., 2022; Rauschkolb et al ., 2022; Zhang & Jiang, 2022). We found that the stimulating effect of elevated CO 2 on aboveground biomass at high levels of inundation was conditional on an additional environmental factor (salinity) and age cohort (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It would be worthwhile, for example, to illustrate how the spatial and temporal scales of environmental change align with genetic and phenotypic variation observed within and among populations of S. americanus (Summers et al ., 2018; Vahsen et al ., 2023). Conducting further empirical work using pedigreed full‐sib and half‐sib families generated from controlled crosses would offer a stronger basis for drawing inferences about the mechanisms underlying patterns of phenotypic variation by, for example, accounting for factors like maternal effects and epigenetic variation ( sensu Preston et al ., 2022) and allowing for further exploration of responses to selection in a quantitative genetics framework.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by current debate surrounding the Trade-off Hypothesis and increasing interest in the evolution of phenotypic plasticity and genetic assimilation under global change (Gunderson and Stillman 2015; Kelly 2019; Sasaki and Dam 2019; van Heerwaarden and Kellermann 2020; Barley et al 2021; Preston et al 2021; Sasaki and Dam 2021), we used simulations to explore the more general consequences of regression to the mean for tests of genetic assimilation at the macroevolutionary level. We conducted simulations that assumed mechanistically different models for plasticity evolution, as well as different experimental sampling designs for measuring species phenotypic traits.…”
Section: Introductionmentioning
confidence: 99%